2013
DOI: 10.5812/jjm.5222
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HIV in Newly Detected Pulmonary Tuberculosis Patients in Khuzestan, Iran: Should HIV Testing Be Included in National Tuberculosis Program in This Region?

Abstract: Background: Human immunodeficiency virus (HIV) testing strategy for tuberculosis (TB) patients in some high HIV incidence countries has been recommended based on interaction between HIV and TB. Objectives: The present study aimed to determine the prevalence of HIV infection among newly detected pulmonary TB patients. Patients and Methods:In a cross sectional study, 104 cases including 95 non injecting drug users (IDU) and nine IDU, from 2009 to 2011 in Ahvaz capital of Khuzestan province in the south west of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…According to the "Administration of Tuberculosis and Leprosy Control" of the Ministry of Health and Medical Education in Iran, in 2010, a total of 10,485 old and new cases of TB were reported in Iran and of these cases, 326 patients (around 2.2%) were HIV positive (34). Thus, due to the low prevalence of HIV infection in Iran, routine HIV testing may not be required for newly detected pulmonary TB patients (35). Bordering on Afghanistan, Pakistan and Iraq, with severely disrupted health services due to war and newly established countries to the north of Iran, have led to high TB infection rate in our country.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the "Administration of Tuberculosis and Leprosy Control" of the Ministry of Health and Medical Education in Iran, in 2010, a total of 10,485 old and new cases of TB were reported in Iran and of these cases, 326 patients (around 2.2%) were HIV positive (34). Thus, due to the low prevalence of HIV infection in Iran, routine HIV testing may not be required for newly detected pulmonary TB patients (35). Bordering on Afghanistan, Pakistan and Iraq, with severely disrupted health services due to war and newly established countries to the north of Iran, have led to high TB infection rate in our country.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variety of BCG vaccine strains may change the resulting immunological response to it. Four common sub-strains that are currently in use are BCG-Pasteur (1173P2), BCG-Japan (Tokyo-172), BCG-Danish (Copenhagen-1331) and BCG-Glaxo (1077) (35). Although in the majority of countries with high TB incidence, the vaccine is supplied by UNICEF/WHO and the Global Alliance for Vaccines and Immunization (GAVI); in Iran as one of those countries with high TB incidence, a local unknown BCG vaccine strain is being used (37).…”
Section: Resultsmentioning
confidence: 99%
“…The current study likewise the other studies showed that IDU either alone or in combination with HIV infection were important risk factors for Pulmonary Tuberculosis among prisoners ( 2 , 11 , 15 , 18 , 19 , 22 , 27 ). Alavi et al in another research in Khuzestan concluded that IDU subjects were significantly at the risk of both TB and HIV infection ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) is a member of lentivirus (a subgroup of retrovirus) that causes progressive degeneration of the immune system, leading to the development of acquired immune deficiency syndrome (AIDS) (Alavi, 2013;Tudela, 2014). HIV has infected more than 60 million and killed 30 million people around the world.…”
Section: Introductionmentioning
confidence: 99%